Analisis Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Perusahaan - Rossi, Rio Novianto; Panggabean, Rosinta Ria (Binus Business Review, 2012)
This study describes the relationship between corporate governance with corporate performance and learns about the development and implementation of GCG in Indonesia. This study uses regression analysis to determine whether corporate governance has a positive influence. Sampling of Corporate Governance Perception Index (CGPI) for 2006 to 2009 from The Indonesian Institute for Corporate Governance (IICG) was used to measure the influence of corporate governance with Tobinâs Q on the performance of the enterprise market and Return On Equity (ROE) was used to measure the operational performance of the company. This study used a sample of 40 companies surveyed by IICG from 2006 to 2009 and included in the top 10 corporate governance ranking index released by IICG and the companiesâ financial reporting are also listed on the BEI (Bursa Efek Indonesia) as well. The sampling method is purposive sampling. The result of this study indicate that there is no significant relationship between corporate governance with Tobinâs Q (market performance) but there is a significant positive relationship between corporate governance with ROE (operational performance).